Macroeconomic factors and household savings: A case study in Malaysia - Shyafina Soleha Mohd Afendi; Sarimah Surianshah; Chong Mun Ho (American Institute of Physics Inc., 2024)
The period of substantial economic ambiguity such as recession and economic crisis had urged us to boost the savings rate as people forgo their current consumption expenditure to compensate for an unpredictable financial future. The exigency of saving amid new normal endemic is vital for economic growth and recovery. Hence, this paper is aimed to analyze some macroeconomic factors such as interest rate, inflation rate, household income, government consumption expenditure, and the household final consumption expenditure that can influence the household savings in Malaysia by using the ordinary least square method (OLS). This paper utilizes the secondary data sources from the World Bank Data and Department of Statistics Malaysia over the period from 1999 to 2019. The findings manifest that a new predictor variable which is the government consumption expenditure, as well as the household final consumption expenditure had a negative significant effect on household savings whereas household income and interest rate are known as less significant factors. Nonetheless, inflation rate is found insignificant towards the household savings in Malaysia. Therefore, this paper implies the exploration of factors affecting household savings could be useful to policymakers, investors, and financial advisors to help sustaining the macroeconomic wellbeing and hence raise the standard of living.